Assessment of the Health-Related Behaviors of Men Practicing Combat Sports and Martial Arts - Dariusz BOGUSZEWSKI; Jakub Grzegorz ADAMCZYK; Dariusz BIALOSZEWSKI (Tehran University of Medical Sciences, 2019)
Background: Physical activeness is one of the main elements of lifestyle in terms of preventing civilization diseases. The main purpose of this study was to assess the selected health behaviors of men practicing combat sports and martial arts and to find out what features or variables may have an influence one's lifestyle. Methods: Overall, 561 men aged 17-35 yr were enrolled and divided into three groups. Studies were conducted from March 2011 to June 2015 in Warsaw, Poland. The main research tool was Juczyński's Health Behaviour Inventory. The questionnaire includes 24 statements - descriptions of various health-related attitudes and behaviours - divided into four categories: proper eating habits, preventive behaviours, positive psychical attitude, and health practices. Results: The persons practicing combat sports and martial arts presented the highest level of health behaviours. The result of Group 1 was significantly higher than the result of Group 2 (P=0.05) and Group 3 (P<0.001). The sportsmen from Group 1 obtained the highest result in the category of psychical attitude (3.5), which was similar to the result of the non-active group (3.29). The men belonging to Group 2 rated highest their eating habits (3.37). All groups obtained the lowest results in the category of preventive behaviours. Conclusion: The men practicing combat sports and martial arts showed high general level of health behaviours. It may give evidence to the intellectualization of sport and health training process, as well as to the fact of adopting the desired behaviours in everyday life.